Regional Integration and Policy Coordination - The Case of Fisheries Policy in the Lake Victoria Region - Andersson,Astrid (2010)
The aim of this thesis is to analyze the extent to which policy integration and project coordination has been achieved and what the effects of these two factors have been in relation to the fisheries sector in the Lake Victoria region in the East African Community (EAC). Theories pertaining to benefits of policy integration and project coordination are utilized as well as the theory of the "Tragedy of the Commons". In the analysis, the role of the Nile Perch - the most exported fish from the Lake Victoria region is emphasized. Furthermore, environmental problems standing in the way of the Lake Victoria fisheries sector as well as issues pertaining to policy integration and project coordination are illustrated. Possible solutions to these problems are then given. The most significant conclusion reached is that policy integration and project coordination has not been achieved to a great extent in relation to the Lake Victoria fisheries sector in the EAC. This is largely due to the fact that the region lacks the finances, infrastructure and will power to deal with the issues.
Keywords: economic systems; economic theory; econometrics; Economics; Tragedy of the Commons; Policy Integration; Project Coordination; Lake Victoria; EAC; economic policy; Nationalekonomi; ekonometri; ekonomisk teori; ekonomiska system; ekonomisk politik